Makna Penderitaan Dan Harapan Dalam Coping Keluarga Kristen Yang Memiliki Anak Autis - Ibrahim Ibrahim; Fonny Natalia Joseph (EULOGIA: Jurnal Teologi dan Pendidikan Kristiani, 2026)
Abstract: Raising children with autism spectrum disorder (ASD) presents various challenges for families, especially in psychological, social, and spiritual aspects. In the context of the Christian family, this experience is processed not only as a burden of care, but also as a battle of faith that includes questions about the meaning of suffering and hope. This article aims to examine how Christian families interpret suffering and hope in dealing with the education of autistic children. This research uses a qualitative-theoretical approach through an interdisciplinary review of the literature that integrates family psychology, road theory and Christian theology. The results of the study show that family coping is collective and is strongly influenced by the religious meaning that the family builds. Suffering can be understood constructively as a space for the transformation of faith and family relationships, while hope, rooted in the Christian faith, plays an important role in building family resilience. This article emphasizes the need for pastoral-theological support, as well as the inclusive and empathetic role of the church, to promote positive religious coping and support the holistic well-being of Christian families with autistic children. Keywords: Autism, Family Coping, Suffering, Christian Hope, Pastoral Theology